Collaboration entre chercheur et acteurs : rôle de l’objet d’étude et de l’observatoire dans une approche « cours d’action » - Nicolas Perrin (Recherches en Éducation)
This contribution questions link between research and training within the empirical program of course-of-action. It is focused first on the definition of the object of study and second on the nature of the activity requested by the observatory's course-of-action. The observatory of course-of-action (Theureau, 2006, 2009b) aims to study the activity of the actors. It implies to go back in dynamic situation using traces to encourage verbalization of the pre-reflective consciousness. A clear distinction is made between then 1) the verbalizations and 2) the analytical commentary or awareness. This distinction is not obvious to fit in the analysis of a training situation. Discussions focus on 1) the relationship between working conditions and the progressive definition of a research object, 2) the activity solicited by the observatory of course-of-action and awareness by the actors at this occasion.